Sustained censorship in IR (2022-09) (Iran) - Voidly (2022)
CRITICAL severity censorship detected in Iran. Confidence: 75%. Data sourced from OONI.
Censorship Incident ID: IR-2022-0005
Keywords: censorship; IR; censorship; critical